2020
DOI: 10.1186/s12263-020-00666-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling and analysis of some miRNAs in subcutaneous white adipose tissue during development of obesity

Abstract: Background MicroRNAs are emerging as new mediators in the regulation of adipocyte physiology and have been approved to play a role in obesity. Despite several studies have focused on microRNA expression profiles and functions in different metabolic tissues, little is known about their response to nutritional interventions in white adipose tissue during obesity stages, and whether they differ in this response to weight-reduction strategy is poorly understood. Our objectives were to study the dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…In our study, interaction effects on T2DM have been demonstrated between miR-133a-2 rs13040413 or let-7a-1 rs13293512 and dyslipidemia. It has been showed that the expression levels of miR-133a and let-7a were in a dysregulation pattern under high lipid condition ( 35 ). Evidence also showed that miR-133a and let-7a were also related to lipid accumulation ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, interaction effects on T2DM have been demonstrated between miR-133a-2 rs13040413 or let-7a-1 rs13293512 and dyslipidemia. It has been showed that the expression levels of miR-133a and let-7a were in a dysregulation pattern under high lipid condition ( 35 ). Evidence also showed that miR-133a and let-7a were also related to lipid accumulation ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Let-7 family is reported to target high-mobility group AT-hook 2 (HMGA2) and is considered involved in adipogenesis, glucose metabolism, insulin resistance, and inflammation [ 133 , 134 ]. A recent study by Youssef et al showed that Let-7 is an important regulator of adipogenesis in 3T3-L1 cells, with Let-7a-5p being downregulated in HFD-fed rats [ 135 ]. Let-7 is upregulated after induction of adipogenesis by either the standard adipogenic cocktail containing dexamethasone, isobutylmethylxanthine, and insulin or the combination of rosiglitazone and insulin [ 133 ].…”
Section: Micro Rnas Regulating Brite Atmentioning
confidence: 99%
“…Increasing data show that this differentiation of pre-adipocytes is further characterized by changes in the miRNA expression profile of WAT, including both upregulated miRNAs (e.g., MiR-103, MiR-107, MiR-143, MiR-26b, MiR-375, MiR-21, MiR-148a, and MiR-30) [ 94 , 142 , 143 , 144 , 145 , 146 , 147 ] and downregulated miRNAs (e.g., MiR-221, MiR-155, MiR-424, MiR-210, and MiR-125b) [ 143 , 148 , 149 ]. As WAT and BAT adipogenesis share common pathways, there is an overlap in the miRNAs identified in both WAT and BAT, which mediate various effects [ 51 , 135 ].…”
Section: Microrna In Watmentioning
confidence: 99%
See 1 more Smart Citation
“…As a primary regulator of lipid and glucose metabolism (Youssef et al. 2020 ), miR-107-5b is also involved in the formation of cholesterol. Studies have found that miR-107-5b can affect the pathogenesis of cholesterol gallstones (Qian et al.…”
Section: Genes That Regulate Glucose and Lipid Metabolismmentioning
confidence: 99%